Down/up-conversion dual-mode ratiometric fluorescence imprinted sensor embedded with metal-organic frameworks for dual-channel multi-emission multiplexed visual detection of thiamphenicol. (15th September 2022) - Fu, Jinli; Zhou, Shu; Wu, Xiaodan; Tang, Sisi; Zhao, Pengfei; Tang, Kangling; Chen, Yu; Yang, Zhaoxia; Zhang, Zhaohui; Chen, Hongjun
Abstract: The establishment of a fluorescence sensing system for sensitive and selective visual detection of trace antibiotics is of great significance to food safety and human health risk assessment. A simple and rapid one-pot strategy was developed successfully to synthesize a down/up-conversion dual-excitation multi-emission fluorescence imprinted sensor for dual-channel thiamphenicol (TAP) detection. In this strategy, the metal-organic frameworks were in situ incorporated into the fluorescence imprinted sensor, guiding the coordination induced emission of abiotic carbon dots and signal-amplification effect of fluorescence sensing. Under dual-excitation (370 nm and 780 nm), the fluorescence imprinted sensor exhibited a dual-channel fluorescence response toward TAP with two-part linear ranges of 5.0 nM–6.0 μM and 6.0 μM–26.0 μM. Significantly, the fluorescence color ranged from blue to purple to red can be observed with the naked eye. The results of the dual-channel TAP determination in actual samples by the fluorescence imprinted sensor indicated that the fluorescence imprinted sensor provided a sensitive, selective, and multiplexed visual detection of TAP in complex sample. Graphical abstract: Image 1 Highlights: A down/up-conversion multi-emission fluorescence imprinted sensor was prepared. The parallel dual-channel visual detection for thiamphenicol was performed. Metal-organic frameworks increased the fluorescence sensitivity of the sensor. A rapid, sensitive, selective and multiplexed analysis for thiamphenicol was provided.